Building Trust For Ijen Merapi Ungup-Ungup Crater Nature Park Development - Nurany, Fierda; Wardiyanto, Bintoro; Setijaningrum, Erna (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to examine trust building and share understanding in the development of Ijen Merapi Ungup-ungup Crater Nature Park. There are allegations of corporate interests behind the expansion of Ijen Merapi Crater Nature Park. This research method is qualitatively descriptive approach through interviews from government, public and private. The results showed in 2020, the Minister of Environment and Forestry changed the main functions of forest areas into nature parks, leading to the formation of trust for the development of this nature park. But not yet formed due to constructive conflicts between stakeholders, egocentric interests, and lack of collaboration.